Memorys Significance in the Formation of Ethnic Identity: A Case Study of Deported Meskhetians Residing in the Samtskhe-Javakheti Region (Global Journal of Human-Social Science, 2024)
This paper examines the role of memory in shaping ethnic identity among deported Meskhetians residing in Georgia's Samtskhe-Javakheti region. Through interviews and analysis, it explores how personal, collective, and historical narratives of the 1944 deportation and origins impact contemporary identity formations. Differences emerge between scholarly perspectives attributing Meskhetian roots to ancient Georgian tribes versus Turkish peoples. Despite varied origin narratives, the shared trauma of deportation serves as a collective touchstone passed down through storytelling and post-memory. Collective trauma is transmitted across generations through stories and shapes the identity of those who did not directly live through the traumatic events themselves. It is an imaginative, creative memory defined by distance from the original events. The paper situates these multifaceted memories and identities within theoretical frameworks on cultural trauma, narrative construction of history, and the complexity of lived versus recorded pasts.
Keywords: meskhetians; ethnic identity; memory; trauma; deportation; narratives; history; postmemory